Heterogeneity and versatility of the extracellular matrix during the transition from pleomorphic adenoma to carcinoma ex pleomorphic adenoma: cumulative findings from basic research and new insights - Scarini, João Figueira; de Lima-Souza, Reydson Alcides; Lavareze, Luccas; Ribeiro de Assis, Maria Clara Falcão; Damas, Ingrid Iara; Altemani, Albina; Egal, Erika Said Abu; dos Santos, Jean Nunes; Bello, Ibrahim Olajide; Mariano, Fernanda Viviane (Frontiers in Oral Health, 2023)
Pleomorphic adenoma (PA) is the most common salivary gland tumor, accounting for 50-60% of these neoplasms. If untreated, 6.2% of PA may undergo malignant transformation to carcinoma ex-pleomorphic adenoma (CXPA). CXPA is a rare and aggressive malignant tumor, whose prevalence represents approximately 3% to 6% of all salivary gland tumors. Although the pathogenesis of the PA-CXPA transition remains unclear, CXPA development requires the participation of cellular components and the tumor microenvironment for its progression. The extracellular matrix (ECM) comprises a heterogeneous and versatile network of macromolecules synthesized and secreted by embryonic cells. In the PA-CXPA sequence, ECM is formed by a variety of components including collagen, elastin, fibronectin, laminins, glycosaminoglycans, proteoglycans, and other glycoproteins, mainly secreted by epithelial cells, myoepithelial cells, cancer-associated fibroblasts, immune cells, and endothelial cells. Like in other tumors including breast cancer, ECM changes play an important role in the PA-CXPA sequence. This review summarizes what is currently known about the role of ECM during CXPA development.